Breakup dynamics of elastic droplet and stretching of polymeric filament in a T-junction. (12th October 2019) - Sun, Xin; Zhu, Chunying; Fu, Taotao; Ma, Youguang; Li, Huai Z.
Graphical abstract: Highlights: Dynamic behaviors between Newtonian and viscoelastic droplets are compared. Interfacial evolution of viscoelastic droplet with polymeric filament is displayed. Effect of elasticity on shrinkage of droplet neck could be not prominent. Elasticity plays an important role in stretching dynamic of polymeric filament. Abstract: Dynamics of elastic droplet breakup and stretching of polymeric filaments in a microfluidic T-junction are investigated experimentally. Through comparisons between cases of Newtonian droplet and a series of viscoelastic droplets with similar shear viscosity, the effect of elasticity on breakup dynamic of droplet is especially focused. Four sequential stages of droplet breakup in a microfluidic T-junction are observed: (I) squeezing, (II) transition, (III) pinch-off and (IV) filament rupture stages. For former three stages (I–III), dynamic behaviors of viscoelastic droplets with lower molecular weight ( M w = 1 × 10 5 g/mol and 3 × 10 5 g/mol) and Newtonian droplet are similar, while for viscoelastic droplet with higher molecular weight ( M w = 1 × 10 6 g/mol), the spatial obstruction of previous filaments accelerates the shrinkage of droplet neck. Additionally, the transformation of dominant force from inertial to capillary force leads to the variation of scaling laws describing the neck evolution. For filament rupture stages (IV), with extension of polymer molecules chain, the elastocapillary balance contributes to the exponential thinning of the polymeric filament, while the width of thread neck decreases linearly with the time for Newtonian droplet. Furthermore, more effort has been devoted to investigate the stretching dynamic of filament. The stretching rate of filament is independent of elasticity, but proportional to two-phase flow rates.